Pediatric Papillary Renal Cell Carcinoma in a Horseshoe Kidney: A Case Report with Review of the Literature - Abelardo Loya-Solis; Lucía Alemán-Meza; Luis Carlos Canales-Martínez; Rodolfo Franco-Márquez; Alim Adriana Rincón-Bahena; Karla María Nuñez-Barragán; Raquel Garza-Guajardo; Marco Antonio Ponce-Camacho (Case Reports in Pathology)
Renal cell carcinoma is the most common malignancy of the kidney in adults. In children, however, it only accounts for an estimated 1.8 to 6.3% of all pediatric malignant renal tumors. Papillary renal cell carcinoma is the second most common type of renal cell carcinoma in children. We present the case of a 12-year-old boy with a 2-month history of abdominal pain, unexplained weight loss, and gross hematuria. Computed tomography revealed a horseshoe kidney and a well-defined mass of 4 cm arising from the lower pole of the right kidney. Microscopically the tumor was composed of papillae covered with cells with abundant eosinophilic cytoplasm and high-grade nuclei with prominent nucleoli. Immunohistochemistry was performed; EMA, Vimentin, and AMACR were strongly positive while CK7, CD10, RCC antigen, TFE3, HMB-45, and WT-1 were negative. Currently, 10 months after the surgical procedure, the patient remains clinically and radiologically disease-free.